The Relationship Between Religion and The State in Indonesia, and Its Relation to Islamic Law - Ahmad Hamidi; Asasriwarni Asasriwarni; Ikhwan Matondang (NEGREI: Academic Journal of Law and Governance, 2022)
The relationship between religion and the state has become an actual and dynamic discourse in every phase of the development of civilization, both in the West and in the East. The debate revolves around the question of the form of the state, whether it is integral, symbiotic, or secular. Departing from this discourse, this study examined the existence of the relationship between religion (Islam) and the state in Indonesia. The approach used was Martin Heidegger's hermeneutics, while the study method used was a comparative method. The results of this study indicate that historically-normatively, the Prophet SAW had formulated the State of Medina based on the Medina Charter which spirit was based on the texts of the Qur'an, not an Islamic state based on the literal Qur'an. The scholars who became the founders of the Indonesian state had also formulated Pancasila as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia as the ideal building for establishing relations between religion and the state in Indonesia, so that religion and the state could develop dialectically. The substance of religious norms was applied after promulgation and in accordance with Pancasila and the 1945 Constitution of the Republic of Indonesia. Therefore, the ideal relationship between religion and the State could be built based on a symbiotic or dynamic-dialectical typology.